New communication strategies of modern classical artists - Vardanyan, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the study: Along with the crisis of the "aging audience" of classical music in concert halls, which is noted by researchers and performers, in the last two years there has been a tendency to increase listening to classical music on digital platforms. The fact that, on the one hand, we are talking about the crisis of classical music audience reduction and, on the other hand, there are opposite trends indicating an increase in its popularity, actualizes the study of the communication mechanisms of classical music performers with the audience through digital tools. Main objective of the study: To identify the trends, principles and mechanisms that have led to the recent increase in the popularity of classical music, particularly through digital tools on social media platforms such as YouTube and Instagram. Methodology: Using the concept of "communication strategy" from the field of strategic management, we analyze the trends observed in the process of transformation of the way classical music performers communicate with the audience in the context of the evolution of media technologies. The study also used empirical (data collection, observation), general scientific (analysis) and theoretical (generalization, systematization) methods. Results and conclusions. Modern media platforms have become a great resource for the promotion of a cultural product. They offer opportunities to reach a multi-billion audience composed of different segments, analytical tools and feedback. The mediatization of cultural space and changes in the psychology of perception of cultural products among new generations require new strategies of communication of classical music performers with the audience. The answer lies in the tendency to create audiovisual content that can be broadly divided into those in which classical music is the central object and those in which it is the background. Reels and Shorts, short videos that use classical music as a background, have become a means of expanding audiences by attracting listeners who were not previously interested in classical music. Audiovisual content featuring classical music is evolving from the traditional concert video to the visualization of music through electronic means, plastic arts (photography, painting) and the creation of videos with a storyline (cinematography). An important trend contributing to the growth of classical music audiences is the combination of classical repertoire with more popular film or cartoon music. The study of communication channels and methods of modern classical music performers with the audience is important in connection with the development of the classical music industry in Ukraine and the development of a strategy for the promotion of Ukrainian classical music products in the world market of music production.